Network Management and Governance in Policy Implementation The Case of Smoking Prevention Programs - Hadorn, Susanne (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book assesses the management and performance of networks in light of the rising popularity of collaborative approaches in public service delivery. It does so by examining the case of smoking-prevention networks in Switzerland. The book considers how network managers can be distinguished based on work-context related factors, and analyses how the interaction of these factors leads to either active or non-active network management within collaborative policy delivery arrangements. It also empirically investigates the effects that network management and other network-level and project-level factors have on the policy output performance of these networks. Adopting a multi-method approach combining a qualitative comparative analysis, case studies as well as Bayesian regressions, the book will appeal to academics and students of public policy, public administration, and public management. It will also be of use to practitioners responsible for the design and the management of policy delivery networks. Susanne Hadorn is Researcher and Policy Evaluator at the KPM Center for Public Management, University of Bern, Switzerland. Her research interests include network governance and management, policy implementation, and health policy.
1. Management and Performance in Collaborative Networks: A Review of the Literature and the Contribution of This Book -- 2. Linking Characteristics of Network Managers' Work Context to Network Management and Project-Level Output -- 3. A Multi-method Approach to Analyze Network Management and Policy Outputs -- 4. Swiss Smoking Prevention Policies -- 5. Connecting Network Managers' Work Contexts with Network Management -- 6. Linking Network-Level and Project-Level Factors to Policy Outputs -- 7. Drivers and Obstacles to Active Network Management and Their Influence on Network Performance -- 8. How to Improve Collaborative Policy Delivery within Networks: Theoretical and Practical Insights.
Keywords: Political planning; Political science; Public administration; Public Policy; Governance and Government; Public Management